Analisis Fluktuasi Harga dan Risiko Pemasaran Cabai Rawit dari Kebun Milik Petani: Studi Kasus di Pasar Ujungberung dan Pasar Caringin Bandung - Annisa Rayhan Gunawan; Raihan Mughny Al-Ghiffari; Saoqi Fathur Rohman; Yati Nurhajati (Indo Publishing, 2026)
Cayenne pepper is a strategic horticultural commodity characterized by highly volatile prices. This study aims to analyze the price fluctuation pattern of cayenne pepper from a farmer-owned garden over a full growing season (November 2025-May 2026), identify the factors causing price fluctuation using a descriptive path analysis framework, and describe the marketing channels and risks faced by the farmer. The study employs a single case study design with Udin Saepudin, a cayenne pepper farmer cultivating a 1,400 m² plot at Kp. Pasir Leutik, Desa Ciporeat, Kecamatan Cilengkrang, Bandung, as the research subject. Data were collected through in-depth interviews, documentation of 30 weeks of sales receipts, and triangulated with official price data from BPS (Statistics Indonesia) and the National Food Agency (Bapanas) price panel for Bandung City. Results show that the farmer's selling price fluctuated between IDR 35,000 and IDR 65,000/kg with a coefficient of variation (CV) of 18.3%. Price fluctuation followed a five-phase seasonal pattern, peaking in December 2025-January 2026 and reaching its lowest point in April 2026. Three main factors driving price fluctuation were identified: harvest volume, production costs and price expectations, and seasonal market conditions. Comparison with BPS/Bapanas data revealed an average farmer's share of 78.0%, indicating relatively efficient marketing channels. Total revenue for one growing season reached IDR 55,719,000 with a net profit of IDR 45,719,000 (457.2% of the production cost of IDR 10,000,000).